Uji Efektivitas Ekstrak Etanol Daun Lire (Hemigraphis repanda (L) Hall F) Sebagai Antipiretik Pada Tikus Putih (Rattus norvegicus) - Rahmat Ismail; Hamidah Sri Supriati; Nurul Hastuti Raun (Universitas Muhamadiyah Manado, 2021)
Fever can be interpreted as a body temperature that is higher (>37°C) than normal temperature because of the temperature control center in the hypothalamus, the temperature control center balances temperature during health or fever by regulating the formation and release of heat. For this reason, the purpose of this study was to determine the antipyretic effectiveness of various concentrations of extracts. In this study, 5% peptone was used to induce fever in 15 white rats which were divided into 5 treatment groups. Groups 1 was given 1% NaCMC as a negative control, groups 2 was given paracetamol 9 mg/200gBB) as a positive control, groups 3 was given 10% lire leaf extract (2 mg/200gBB), groups 4 was given 20% lire leaf extract (4 mg/200gBB), and groups 5 was given 40% lire leaf extract (8 mg/200gBB). This results of this study obtained extract levels of 7,44% and there was a weak antipyretic effect at concentrations of 10% and 20% lire leaf extract, while the greatest antipyretic effect was found in 40% lire leaf extract, almost comparable to 9 mg paracetamol.